Bird uncaged : an abolitionist's freedom song - Peterson, Marlon (Bold Type Books, 2021)
A leading advocate for prison abolition and transformative justice shares insights from the author's firsthand experiences of growing up in a violent neighborhood and surviving a brutal incarceration.